On Generalized Approximative Properties of Systems - Turab Mursal Ahmedov; Zahira Vahid Mamedova (International Journal of Mathematics and Mathematical Sciences)
Generalized concepts of b-completeness, b-independence, b-minimality, and b-basicity are introduced. Corresponding concept of a space of coefficients is defined, and some of its properties are stated.